ReSC: a distributed operating system for parallel and distributed applications - Shinjo, Y.; Kiyoki, Y. (Parallel and Distributed Information Systems, 1st International Conference On, 2002)
Summary form only. ReSC is a distributed operating system for both parallel/distributed applications and sequential applications. The hardware environment of ReSC is a set of shared-memory multiprocessors and uniprocessors which are connected to a high-speed local area network. To execute parallel/distributed application programs efficiently, those programs should control scheduling and mapping of their processes by themselves. ReSC provides facilities that enable each application program to control scheduling and mapping. The authors refer to the module which controls mapping as a distribution optimizer. In ReSC, each parallel/distributed application program can include its own lightweight process scheduler and distribution optimiser for optimal mapping and scheduling. ReSC supports for them by kernel calls and libraries. They have developed a lightweight process library on Sequent Balance 8000 and Omron Luna88k (which are shared-memory multiprocessors), Sun4, Sun3 and NeXT. By using the library, they have built a parallel processing system for databases.< >